Implementasi nilai pendidikan karakter cinta tanah air pada pembelajaran tatap muka terbatas di sekolah dasar - Syahputri, Khoerinisa Kiky Azizy; Istiyati, Siti; Kamsiyati, Siti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the implementation of the character education value of love for the homeland at Mangkubumen Kidul Surakarta. This research is a qualitative research. The subjects of this study were students of class IVB Elementary School Mangkubumen Kidul Surakarta, totaling six student respondents. Data collection techniques in this study used interviews, observations, and questionnaires. The validity of the data in this study used technical and time triangulation. Data analysis used the Miles-Huberman interactive analysis model. The results of this study indicate that in the implementation of the character education value of love for the homeland, student respondents can act to accept the diversity with a percentage of 80%; using domestic products with a percentage of 100%; imitate the value of heroism with a percentage of 84%; memorized the national anthem with a percentage of 74%; build a person who likes to learn with a percentage of 87%; and prioritize the public interest over personal or group with a percentage of 49%. Based on the average data obtained, it can be identified that the love of the homeland character education has been implemented very well.